2018
DOI: 10.1590/1983-40632018v4851297
|View full text |Cite
|
Sign up to set email alerts
|

Quality of bananas harvested at different development stages and subjected to cold storage

Abstract: One of the biggest problems faced by banana growers is to determine the most appropriate harvest time. This study aimed to evaluate the post-harvest conservation of 'Prata-Anã' bananas harvested at 16, 17, 18, 19 and 20 weeks after the inflorescence emergence and subjected to 25 days of cold storage at the temperature of 13.5 ºC (± 1 ºC) and 90 % (± 5 %) of relative humidity. The bananas harvested at 19 and 20 weeks after the inflorescence emergence showed a more advanced maturity stage after 25 days of cold s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(14 reference statements)
0
1
1
3
Order By: Relevance
“…10). The results found in this study are lower than those observed by Santos et al [26], who also reported an increase in total sugar values over the evaluation days, ranging from 4.05% to 25%. According to Silva et al [17], while amide is hydrolyzed, there is an increase in total sugar content, which makes fruits ripe and sweet.…”
Section: Resultscontrasting
confidence: 99%
“…10). The results found in this study are lower than those observed by Santos et al [26], who also reported an increase in total sugar values over the evaluation days, ranging from 4.05% to 25%. According to Silva et al [17], while amide is hydrolyzed, there is an increase in total sugar content, which makes fruits ripe and sweet.…”
Section: Resultscontrasting
confidence: 99%
“…Os resultados de SST também foram inferiores aos verificados por Vilete et al (2016), Araújo e Nassur (2017) e por Viana et al (2017), entretanto, foi superior aos encontrados por Castricini et al (2016) para as colheitas realizadas aos 90, 110 e 130 dias após a floração. Os SST são utilizados como uma medida indireta do teor de açúcar e aumentam com a maturação dos frutos, em decorrência de processos sintéticos ou degradação dos polissacarídeos (CHITARRA;CHITARRA 2005;SARMENTO et al, 2015;SANTOS et al, 2018). Segundo Hanson et al 2012, frutos com maiores teores de SST são mais desejáveis, pois promovem melhor sabor para o consumo, seja in natura, fritos, cozidos ou industrializados.…”
Section: Resultsunclassified
“…Os resultados deste parâmetro foram menores que os obtidos por Castricini et al (2015), que aferiram valores de 74,43 a 77,12 com diferentes idades de colheita e por Castricini et al (2016), que observaram médias de 70,43 a 72,96 com diferentes cultivares na época de colheita comercial e no estágio de maturação VI, indicando que a casca do fruto com tonalidade amarela foi mais brilhosa que a deste trabalho. Já para a cromaticidade, o valor médio ficou entre os 35,40 e 54,59 encontrados por estes autores, e acima dos obtidos por Santos et al (2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The firmness loss in fruits is generally associated with the action of pectinolytic enzymes which leads to destabilization of the cell wall. According with [52], mean values of firmness can be found in banana cv. 'Prata-Anã' ranged from 32.8 N ~ 40 N at 25 days of refrigerated storage under 13.5 °C.…”
Section: The Role Of Hydrothermal Treatment and Cacl 2 In The Physicamentioning
confidence: 99%